"Home-grown" jihad understanding Islamist terrorism in the US and UK - Mullins, Sam (Imperial College Press, 2016)
The book analyzes the background and operational activities of nearly 800 American and British jihadis who mobilized between 1980 and September 11th 2013, including factors such as mental health, education, processes of radicalization, leadership, use of the Internet, sources of funding and links to foreign terrorist organizations.